Institutional Quality and Financial Development in West Africa Economic and Monetary Union (Global Journal of Management and Business Research, 2020)
Having become aware of the financial status of underdeveloped countries of the West African Economic and Monetary Union (WAEMU) and the potential role of institutional factors in the effectiveness of financial development policies, this study proposes an analysis of the impact of institutional quality on the success of their financial development policy. The results of the study show that institutions have a decisive impact on the finance effect on economic growth and development. The study explains that since independence (1960) to the present, various financial development policies have not paid off. The author,
Keywords: institutional quality; financial policy development; static and dynamic panel; a composite indicator of financial development